Spatially nested niche partitioning between syntopic grazers at foraging arena scale within overlapping home ranges. - Owen-Smith, N.; Martin, J.; Yoganand, K. (Ecological Society of America, 2015)
Niche separation among species with similar resource requirements can be expressed at various spatiotemporal scales, from the resource components selected at feeding sites to habitat and home range occupation and ultimately geographic distribution ranges. African large herbivores present a challenge to niche theory because multiple species commonly overlap both spatially and in vegetation components consumed. Aided by GPS telemetry, we investigated the space use patterns of two large grazers that are frequently associated in mixed-species aggregations. Specifically, we compared a generalist grazer with hindgut fermentation (plains zebra) with a similar-sized grazing ruminant (blue wildebeest) in west-central Kruger National Park, South Africa. We found that herds of the two species overlapped substantially in the home ranges that they occupied, but exploited spatially distinct foraging arenas for periods lasting several days or weeks within these ranges. Moreover, wildebeest and zebra differed in duration of settlement, extent of areas occupied during settlement, consequent exploitation intensity per unit area, proportion of time spent within foraging arenas relative to roaming interludes, and movement rates while within these arenas. In particular, wildebeest herds concentrated within small areas for prolonged periods, while zebra herds used more foraging arenas but exploited them for briefer periods. Both species overlapped substantially in habitat use, although wildebeest more strongly favored gabbro uplands and sodic sites presenting short grass lawns while zebra made greater use of areas with a taller grass cover. Hence resource partitioning was expressed mainly through behavioral distinctions in patch exploitation at foraging arena scale rather than in home range or habitat separation. Although zebra may have been partially excluded from the grasslands kept short by wildebeest, these sites formed only a small part of the wider ranges utilized by zebra, thereby restricting the competitive consequences. Hence spatially nested resource partitioning of this form contributes to the coexistence of these two grazers, and may be a mechanism enabling niche separation among other species.
Keywords: Competition; Connochaetes taurinus; Equus zebra; Facilitation; Foraging arena; GPS telemetry; Home range; Kruger National Park; Large mammalian herbivores; Niche separation; Spatial partitioning